2006
DOI: 10.3989/gya.2006.v57.i4.65
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on yield and quality of <i>Moringa oleifera</i> seed oil

Abstract: RESUMENEfecto de la salinidad en la producción y calidad del aceite de semilla de Moringa oleifera.Ha sido examinada la variación en la producción y composición del aceite de semilla de Moringa oleifera extraído a partir de semillas cultivadas en Pakistan con diferente concentración salina en el cultivo. La producción obtenida por extracción con hexano fue de 33.50% y 32.79% respectivamente para las semillas cultivadas en áreas con alto y bajo contenido salino. El análisis de la varianza (ANOVA) reveló la inex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
(34 reference statements)
5
8
0
1
Order By: Relevance
“…In the present study, salt stress significantly increased α‐ and γ‐tocopherol contents in the seed oil of both sunflower hybrids. These results are in agreement with those of Anwar et al ,58 who reported that salt stress increased tocopherol content in the seed oil of Moringa oleifera plants. A considerable variation was observed in both sunflower cultivars with regard to this attribute.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, salt stress significantly increased α‐ and γ‐tocopherol contents in the seed oil of both sunflower hybrids. These results are in agreement with those of Anwar et al ,58 who reported that salt stress increased tocopherol content in the seed oil of Moringa oleifera plants. A considerable variation was observed in both sunflower cultivars with regard to this attribute.…”
Section: Discussionsupporting
confidence: 93%
“…However, there were significant (P 0.05) differences in color (15.00R + 70.00Y and 12.80R + 60.00Y), free fatty acid (0.6 and 4.6% as oleic acid) and saponification (170.2 and 183.3 mg of KOH/g of oil) values of oils from saline and non-saline Values are mean AE SD of five cotton seed samples from each of the saline and non-saline areas, analyzed individually in triplicate NS non-significant regions, respectively. These findings are in good agreement with our previous findings on Moringa oleifera oil [22]. There was a significant (P 0.05) variation in the oxidation values of specific extinctions at 232 and 270 nm ( Table 5), which reveal the oxidative deterioration and purity of the oils [23].…”
Section: Proximate Composition and Physico-chemical Properties Of Cotsupporting
confidence: 92%
“…The levels of a-tocopherol, which has the greatest vitamin E potency [25], and c-tocopherol, of cottonseed oils from the saline area were significantly (P 0.05) higher as compared to those from the non-saline area, which could be attributed to the effect of salinity stress. The high a-tocopherol contents of Moringa oleifera seed oil from saline areas has also been reported [22].…”
Section: Proximate Composition and Physico-chemical Properties Of Cotmentioning
confidence: 76%
“…Salt affects the photosynthesis apparatus but the researchers are still unclear about the factors, which are responsible for the inhibition of photosynthetic activity (Steduto et al, 2000). Also, Anwar et al (2006) found no significant variation in the moringa protein contents from saline and non-saline areas.…”
Section: Effect On Leaves Chemical Constituentsmentioning
confidence: 88%